Por un arte al servicio del pueblo: Frente Nacional de Artes Plásticas (1952-1963), de Raúl Cano Monroy (REVISTA NODO, 2026)
The book offers an in-depth look at the history of the National Front of Plastic Arts, a group that, between 1952 and 1963, promoted Mexican art nationally and internationally, defending realism as the predominant style.